Looking Back into an Action-Research Project: Teaching/Learning to Reflect on the Language Classroom - Lopes, Luiz Paulo da Moita; Freire, Alice Maria da Fonseca (The ESPecialist, 2012)
This paper focusses on an action-research project in language classrooms in the official educational system of the city of Rio de Janeiro. It introduces the demand which motivated the project and the general theoretical framework which underlies action-research as reflection on a social practice conducted by its participants. Next, the paper reports on the general plan of the project, involving issues connected with the research context, length of time and the steps followed. By way of conclusion, positive and negative factors of the project are drawn on the basis of an analysis of data derived from audiotaped sessions with participants, open-ended questionnaires and the research papers produced.